O10 Characteristics of patients who discontinued baricitinib treatment within 12 months and reasons for discontinuation: real-world data. (26th April 2021) - Lwin, May Nwe; Holroyd, Christopher; Edwards, Christopher J
Abstract: Background/Aims Baricitinib is an oral targeted synthetic disease-modifying anti-rheumatic drug (tsDMARD) recommended by the National Institute for Health and Care Excellence (NICE) in the UK for severe rheumatoid arthritis (RA) either as mono- or combination therapy. We wanted to observe the frequency of discontinuation in a real-world setting, the characteristics of patients who stop taking baricitinib, and the reasons for discontinuation. Objective: To describe the characteristics of patients who discontinue baricitinib treatment and the reasons for discontinuation. Methods A real-world retrospective observational study of baricitinib use in RA patients at University Hospital Southampton using local advanced therapy database for data collection. We described the characteristics of patients discontinuing baricitinib therapy and divided patients into two groups. Group 1 (those who discontinued therapy within the first 12 months of use) and group 2 (who continued therapy beyond 12 months) Results From October 2017 to July 2020, a total of 83 patients started baricitinib and were recorded in the database, 55 (66.27%) remain on treatment to date. Among 28 (33.74%) patients who stopped baricitinib, 21 had stopped within 12 months. The reasons for discontinuation were lack of efficacy (64.28%) and AEs (28.57% - 1 tooth infection, 1 urinary tract infection, 1 discitis, 2 chest infection, 1 personality change, 1 deranged liver function and 1 lymphoma). In group 1, the mean (±SD) age was 49.00 (13.65) years, 66.67% were female and 85.71% were previously biologic inadequate responders (IR), 42.86% were receiving monotherapy, with 57.14% being on combination therapy with a csDMARD and 9.52% were using a glucocorticoid. In group 2, 82.26% were female, 61.52 (10.94) years of age and 83.87% were previously biologic IR, 41.94% were on monotherapy and 58.06% on combination therapy with a csDMARD. Patients who discontinued appeared more likely to be younger and male. However, there was no significant difference regarding mono- or combination therapy, disease duration or seropositivity (p-value > 0.05) (Table 1). Conclusion In a real-world setting, baricitinib appears efficacious and well-tolerated in the first year of use by two-thirds of patients. Characteristics such as older age and female gender were associated with continued use. Disclosure M. Lwin: None. C. Holroyd: Honoraria; Lily. Member of speakers' bureau; Lily. C.J. Edwards: Honoraria; Abbvie, Biogen, BMS, Celgene, Fresenius, GSK, Janssen, Lilly, Mundipharma, Pfizer, Roche, Sanofi, UCB. Member of speakers' bureau; Abbvie, Biogen, BMS, Celgene, Janssen, Lilly, Sanofi, Pfizer, Roche. Grants/research support; Abbvie, Biogen, Pfizer.